3,3-Bis[(4-chlorophenyl)sulfanyl]-1-methylpiperidin-2-one - Zukerman-Schpector, J.; De Simone, C.A.; Olivato, P.R.; Cerqueira, C.R.; Santos, J.M.M.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The piperidone ring in the title compound, C(18)H(17)Cl(2)NOS(2), has a distorted half-chair conformation. The S-bound benzene rings are approximately perpendicular to and splayed out of the mean plane through the piperidone ring [dihedral angles = 71.86 (13) and 46.94 (11)degrees]. In the crystal, C-H center dot center dot center dot O interactions link the molecules into [010] supramolecular chains with a helical topology. C-H center dot center dot center dot Cl and C-H center dot center dot center dot pi interactions are also present.